Perioperative fluorocholangiography with routine indication versus selective indication in laparoscopic cholecystectomy - Guerra-Filho,Vicente (2007)
BACKGROUND: The use of routine or selective peroperatory cholangiography in cholecystectomy is a matter of controversy in literature. AIM: To compare the efficacy of selective or routine fluorocholangiography in diagnostic of common bile duct stone in patients underwent to laparoscopic cholecystectomy based on selective indication criteria. METHOD: Two hundred and fifty four patients with cholelithiasis were prospectively studied. The patients were divided in two groups: to the first 127 patients perioperative fluorocholangiography was indicated as routine (group 1), and to the other 127 patients perioperative fluorocholangiography indication followed clinical criteria (jaundice, choluria, fecal acholia and history of pancreatitis), laboratory criteria (increase in seric alkaline phosphatase, bilirubins, amylase) or ultra-sonographyc criteria (less than 6 mm diameter calculi, common bile duct stone, common bile duct diameter more than 6 mm). A comparative assessment of the difference in common bile duct stone diagnosis, fluorocholangiography success index and reliability of the selective criteria of indication for perioperative fluorocholangiography was compared between the two groups. RESULTS: Perioperative fluorocholangiography was successfully performed in 102 of the 127 patients from group 1 (a rate of 80.3%), and in 59 of the 71 patients from group 2 (a rate of 83.1%). In the 102 patients of group 1 who underwent perioperative fluorocholangiography, 11 (10.8%) presented common bile duct stone, 4 (3.9%) presented common bile duct dilatation, and 1 (1%) had a false-positive image. In the 59 patients from group 2, 7 (11.7%) presented common bile duct stone and one (1.7%) presented a common bile duct diatation. In another situation, when application of selective indication criteria to perioperative fluorocholangiography was simulated in group 1 patients, we observed that only in one patient with common bile duct stone the diagnostic would not have been made. Fluorocholangiography selective indication criteria presented sensitivity of 90.9% and specificity of 46.2%. The main causes of fluorocholangiography failure were biliary pedicle inflammation and cystic duct size and caliber variations. CONCLUSION: There was not a significant difference in common bile duct stone diagnostic through perioperative fluorocholangiography between the groups of patients with selective and routine indication, validating the examination selective indication criteria, with a sensitivity of 90.9%, despite the specificity of 46.2 % - 43 patients were selected to the flourocholangiography and common bile duct stone was not diagnosed.